The Impact of COVID-19 Pandemic on Individuals With Pre-existing Obsessive-Compulsive Disorder in the State of Qatar: An Exploratory Cross-Sectional Study - Siddiqui, Maryam; Wadoo, Ovais; Currie, James; Alabdulla, Majid; Al Siaghy, Areej; AlSiddiqi, Abdulkarim; Khalaf, Eslam; Chandra, Prem; Reagu, Shuja (Frontiers in Psychiatry, 2022)
Background Published evidence about the impact of the COVID-19 pandemic on Obsessive-Compulsive Disorder (OCD) is conflicting. Most studies suggest an increase in the severity of OCD in people with pre-existing OCD, whereas some do not. Aim Given the conflicting evidence globally and lack of data from the Arab world, we aimed to explore the impact of the pandemic on obsessive-compulsive symptoms in adults with pre-existing OCD. Methods A telephonic questionnaire-based cross-sectional study among adults with pre-existing OCD and specifically with fear of contamination and washing compulsions being major symptom dimensions of OCD. The severity of OCD during the pandemic was compared with their pre-pandemic scores. The severity of OCD was assessed using the Yale-Brown Obsessive-Compulsive Scale (YBOCS). Results Those with the duration of diagnosis of OCD of<10 years showed a statistically significant increase in the mean YBOCS score of 5.54 from pre-pandemic to during pandemic, which was significant at p = 0.006. This significance was maintained across the Compulsive and Obsessive subsets of the scale. Conclusion Adults with pre-existing OCD with fear of contamination reported a statistically significant increase in severity of obsessive-compulsive symptoms only if the duration of their OCD diagnosis was relatively shorter (<10 years). In the context of the conflicting evidence regarding the worsening of OCD symptoms due to the unique infection control measures of this pandemic, this study highlights the importance of the impact of the duration of the disorder and the subtype of the disorder. Such classification might help public health resources to be directed better at those most at risk and also help us understand the very nature of this disorder better.